Effective import substitution in the market of agro-food products and the development of export potential - Aiesheva, G.A.; Sultanova, Z.Kh.; Aimukhanbetova2, G. (BUKETOV BUSINESS REVIEW, 2018)
The article considers issues of providing the economic and social security which are consequence of import substitution. As stated in the article, import substitution enhances the competitiveness of different sectors of the national economy and, in finally, allows to take own place on the world market for goods and services. The content of definitions such as import substitution, import substitution policy, export potential was considered. The authors consider various interpretations of these concepts, give their assessment. Different methods for dealing with this problem were cluster-by-cluster described. Particularly issues of import substitution in sphere of APC, ways of its solving both in the republic and CIS countries were detailed analyzed. It was pointed out that one of the most powerful methods to solve this problem is improvement to the system of the regulation and support of agricultural production. Conditions and drivers of supporting APC in the republic were considered. It was indicated that capacity-building should be provided taking account of all regions. Was noted that it is necessary to form the export food potential of the country and its regions, which implies the possibility of carrying out an active export policy in the future, both at the state level and at the level of a separate region, supported by economic diplomacy, internal institutional measures, and a comprehensive regulatory mechanism